IoT-Based Real-Time Monitoring and Thermal Performance Evaluation of A Box-Type Solar Cooker - Panigrahi, Badri N.; Mahanta, Satyam S.; Nayak, Jayashree; Sahoo, Sudhansu S.; Choudhury, Balaji K. (Journal of Applied Science, Engineering, Technology, and Education, 2025)
This work presents the development and evaluation of an IoT-based real-time monitoring system integrated with a box-type solar cooker to assess its thermal performance. The system incorporates an ESP8266 microcontroller interfaced with a DHT11 sensor for ambient temperature and humidity, a DS18B20 sensor for absorber plate temperature, and a MAX6675 with a K-type thermocouple for vessel (water) temperature measurement. All of the sensor data is transmitted to the ThingSpeak cloud platform, enabling real-time visualization and remote analysis. Thermal performance indicators were derived from the recorded data, including the first figure of merit (F₁), second figure of merit (F₂), thermal efficiency (η), and the overall heat loss coefficient (UL). Under clear-sky conditions, the cooker reached a stagnation temperature of approximately 130°C, with ambient conditions near 35°C and solar irradiance around 850 W/m². The calculated F1 (~0.11 °C•m²/W), F2 (~0.41), average thermal efficiency (~30 %), and average heat loss factor (~4.8 W/m²•°C) signify a reasonably efficient solar cooker design. Additionally, real-time insights into heat retention and loss were made possible through continuous monitoring. The integration of IoT with the solar cooker not only improves data acquisition and performance evaluation but also demonstrates the viability of smart sustainable cooking technologies in modern applications. It allows for easy and better evaluation of the cooker by the general user